دور الذكاء الاصطناعي والواقع الافتراضي في دعم وتطوير مهارة اتخاذ القرار لدى لاعبي كرة السلة أكابر. - نباتي الشرقي بلال (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
هدفت هذه الدراسة إلى معرفة دور الذكاء الاصطناعي والواقع الافتراضي في دعم وتطوير مهارة اتخاذ القرار لدى لاعبي كرة السلة أكابر. اعتمدنا المنهج الوصفي واستعملنا أداة الاستبيان، وشملت العينة 26 لاعبا من جمعيتي آفاق مستغانم وأولمبيك شباب مستغانم. أظهرت النتائج أن الذكاء الاصطناعي يساعد على تحليل اللعب وتنظيم الدفاع، بينما الواقع الافتراضي ما يزال محدود الاستخدام رغم فوائده. كما تبين وجود حاجة لتعزيز الجانب الإدراكي للاعبين لتحسين اتخاذ القرار. توصي الدراسة بإدماج التقنيات الحديثة بشكل فعال في الحصص التدريبية. // // // // // // // Abstract This study aimed to explore the role of artificial intelligence and virtual reality in supporting and enhancing decision-making skills among senior basketball players. A descriptive method was adopted, and a questionnaire tool was used. The sample consisted of 26 players from the clubs Afak Mostaganem and Olympique Chabab Mostaganem. The results revealed that AI helps in game analysis and defensive organization, while virtual reality remains underutilized despite its potential. Findings also indicated a need to strengthen players’ cognitive skills to improve decision-making. The study recommends integrating modern technologies effectively into training programs.
LES-2025-19
Keywords: الذكاء الاصطناع; الواقع الافتراضي; مهارة اتخاذ القرار; لاعبي كرة السلة أكابر